Peran Guru Muatan Lokal Agama dalam Memotivasi Anak Belajar Al-Qur'an di Madrasah Ibtidaiyah (MI) Al-Fatah Japanan Mojowarno Jombang - Abdul Rouf; Muhtadi Muhtadi (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2023)
This study aims to describe the role of religious local content teachers in motivating children to learn the Qur'an at Madrasah Ibtidaiyah (MI) Al-Fatah Japanan Mojowarno Jombang. This research use desciptive qualitative approach. The data collection uses observation, interview, documentation and questionnaire techniques, with inductive analysis techniques and relative frequency distribution. The research results show that: (1). Profile of teachers of local religious content at Madrasah Ibtidaiyah (MI) Al-Fatah Japanan Mojowarno Jombang not only teaches the Koran but also teaches Al-Qur'an Hadith and Fiqh subjects. (2). The motivation of children to learn the Qur'an at Madrasah Ibtidaiyah (MI) Al-Fatah Japanan Mojowarno Jombang can be said to be quite good. This can be seen from the results of distributing the questionnaire to 25 students or respondents, that the learning motivation of children in the high category reached 12%, the medium category reached 72%, and the low category reached 16%. (3). The role of the religious local content teacher in motivating children to study the Qur'an at Madrasah Ibtidaiyah (MI) Al-Fatah Japanan Mojowarno Jombang is: (a) providing guidance. (b) creating a conducive and enjoyable classroom atmosphere. (c) give an assessment.